Model of absorbed gamma radiation in the interaction with rock formation - A. A. Azaryan; A. N. Gritsenko; A. A. Trachuk; V. M. Serebrenikov; D. V. Shvets (IAES International Journal of Robotics and Automation (IJRA), 2019)
The article discusses issues of improving the accuracy of operational quality control of iron ore in mountain ranges. There was proposed the use of the absorbed gamma radiation indicator as an improvement of the nuclear physics method for determining the iron content in ore mass are proposed. There were obtained the relationships of the sensitivity of the absorbed gamma radiation intensity on the distance between the detector and the irradiated surface, as well as on the distance between the source and the detector of gamma radiation.